MONITORING AND SELF-ASSESSMENT OF PHYSICAL FITNESS AND DEVELOPMENT OF MOTOR SKILLS OF YOUNG HANDBALL PLAYERS (Physical Culture and Sport: Scientific Perspective, 2025)
The article is devoted to the issues of monitoring and self-assessment of physical fitness and development of motor skills in young handball players. In particular, modern approaches to monitoring the training process are considered, which allow assessing the level of physical qualities of athletes and ensuring individualization of training. Special attention is paid to monitoring methods that contribute to an objective assessment of results, as well as the possibility of involving athletes themselves in the process of self-analysis of their achievements, which increases their motivation for further improvements. The article also considers the criteria for assessing physical fitness, which allow identifying the strengths and weaknesses of handball players' fitness and adjusting their training process. The results of the study may be useful for coaches and specialists working with young athletes, as well as for improving the system of physical training in team sports. The relevance of this problem lies in the need to improve monitoring methods and self-assessment, which will increase the effectiveness of physical training of young handball players and ensure their success in competitions. The problem of monitoring and self-assessment becomes relevant, since it directly affects the effectiveness of sports education and training. At the current stage of development of pedagogical science, the role of individualization of the training process is increasing, which involves taking into account the physical capabilities of each player and the use of adapted methods for assessing his physical fitness. Traditionally used monitoring methods often do not give sufficiently accurate results for assessing the dynamics of the development of motor skills, and also do not provide proper participation of the athlete in the process of independent analysis of his achievements.
Keywords: motor activity; handball; teenagers; training process; monitoring; self-assessment of physical fitness; development of motor skills; young handball players